On the perceptions and conceptions of tourists with regard to global environmental changes and their consequences for coastal and marine environments: A case study of the northern São Paulo State coast, Brazil. (July 2015) - Ghilardi-Lopes, Natalia Pirani; Turra, Alexander; Buckeridge, Marcos S.; Silva, Amanda Cristina; Berchez, Flávio Augusto de Souza; de Oliveira, Valéria Marques
Abstract: A study on the public׳s perceptions and conceptions of global environmental changes (GECs) is relevant to guide future educational strategies and management actions. The present study aimed to: (1) evaluate coastal tourists׳ conceptions and perceptions of GECs; (2) correlate the conceptions presented by tourists about GECs and their self-declared knowledge; (3) evaluate how these tourists perceive their personal contribution to GECs; and (4) verify the frequency at which the media exposed the tourists to information about the influence of GECs on coastal and marine environments. A structured questionnaire was applied to 183 coastal tourists. There was a weak but significant positive correlation ( r 2 =0.152, p <0.001) between self-declared knowledge and the actual conceptions of tourists about GECs and about the sea. Tourists underestimate their role in GECs, pointing out fewer individual actions that contributed to GECs in the questionnaire than expected. Many tourists declared they had never heard of some subjects related to GECs and coastal environments. This study revealed that coastal tourists are still not well informed about their role in GECs and also on their consequences to the society, thus emphasizing the need of more intensive and effective coastal and marine environmental education strategies. Highlights: Environmental perception studies should precede the proposition of environmental education strategies. Coastal tourists׳ conceptions and perceptions of climate change were evaluated. A structured questionnaire was applied to 183 tourists who participated in the Subaquatic Trail Project. Deficiencies in the conceptions were observed; and. Participants had never heard of some of the presented subjects.